Nature of the of polymorphism of salt crystals in the aspect of arborization diagnostic method - Yu. V. Pivovarenko (Морфологія, 2016)
Background. A method of medical diagnostics, called arborization (or ferning), is widely used. Despite this, nature of arborization of biological liquids remains unclear. As it is not enough, we tried to reveal the physical basis of arborization. Objective. To make known the physical and chemical bases of salts polymorphism, including arborization. Results. It was found that a crystal shapes that had been formed upon evaporation of saline solutions depends on the value of the electric potential of such solutions also on the value of the electric charge of the surface on which crystals are formed. It has been particularly found that the evaporation of solutions with positive electric potential is accompanied by the formation of cubic crystals and the evaporation of solutions with negative electric potential is accompanied by the formation of needle-like crystals. It was shown that the cubic crystals of NaCl, the basic salt component of human biological fluids, are formed on the positively charged surface of activated carbon. It was also shown that the needle-shaped crystals of NaCl are formed on the negatively charged surface of silica gel. Conclusion. Various forms of the crystals formed during evaporation of biological liquids of women, reflect the cyclic change in electric potential in such liquids during the menstrual cycle.